Changing precipitation regimes and the water and carbon economies of trees - Oliveira, Rafael S.; Christoffersen, Bradley O.; de V. Barros, Fernanda; Teodoro, Grazielle S.; Bittencourt, Paulo; Brum-Jr, Mauro M.; Viani, Ricardo A. G. (Theoretical and experimental plant physiology, 2014)
Climate change is predicted to affect the water balance of several ecosystems mostly through changes in the energy budget and hydrological input (rainfall frequency, intensity, and timing). Changes in rainfall patterns and cloudiness directly affect incoming radiation, atmospheric water vapor saturation deficit and soil water availability, the main variables controlling the rates of water uptake and transport along the soil–plant–atmosphere continuum (SPAC). Developing a predictive framework about vegetation responses to a changing climate is challenging because it involves complex non-linear interactions between these environmental variables and species-specific responses. By examining the hydraulic traits of functional groups within plant communities we can better predict the impacts of changes in rainfall regimes within functional groups and therefore, generate more realistic predictions of ecosystem carbon and water balance changes due to local and regional changes in precipitation regimes. In this review, we discuss several aspects of plant hydraulic functioning and then explore how predicted changes in precipitation regimes may affect tree water and carbon balance. We examine the impacts of changes in rainfall patterns on the SPAC and also explore the multiple ways that plants can absorb and transport water. Finally, we explore the diversity of hydraulic traits and potential mechanisms causing large-scale drought-induced mortality recently observed in several ecosystems.